Letter from the Minister of Culture and Education to Georg Bredig (1939)
The Ministry of Culture and Education under the Third Reich grants Georg Bredig (1868-1944) permission to move his place of residence abroad to Holland for a period of two years. Georg Bredig would eventually stay in the Netherlands with fellow friend and chemist, Ernst Cohen (1869-1944), while awaiting departure to the United States. Evident in this document is the Third Reich's antisemitic name law that came in to effect on August 17, 1938. All Jews were required to change their first name to a name present on an officially approved list of Jewish names. Having grown up in a Jewish community in Glogow, Silesia, Georg Bredig was forced to re-adopt the ceremonial Jewish name, Salomon, that was given to him at birth.
Keywords: Third Reich; Antisemitism; Jews, German; Jewish Holocaust (1939-1945); Bredig, Georg, 1868-1944